2019
DOI: 10.3390/ijerph16234606
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Healthcare Resources in China: The Spatial–Temporal Evolution and Its Spatial Drivers

Abstract: This paper estimated and evaluated the spatial–temporal evolution of the concentration of healthcare resources (HCRs), in 31 provinces in China between 2004 and 2017, by using the entropy method. The spatial Durbin model (SDM) was used to further analyze the mechanisms behind the spatial driving forces at the national and regional levels. The findings revealed that: (i) The concentration of HCRs differed significantly among eastern, central, and western regions. The eastern, followed by the central region, had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…We used the entropy method and drew on the indicators determined by researchers [ 17 ] to measure health resource agglomeration capacities ( Table 1 ). The entropy method mainly determines the objective weight according to the index variability.…”
Section: Methods and Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the entropy method and drew on the indicators determined by researchers [ 17 ] to measure health resource agglomeration capacities ( Table 1 ). The entropy method mainly determines the objective weight according to the index variability.…”
Section: Methods and Data Sourcesmentioning
confidence: 99%
“…Learning from the research of scholars (Guo, et al, 2019) [17], we selected six factors influencing the spatial correlation network of health resource agglomeration capacities as follows. (1) Level of economic development: the higher the level of economic development, the stronger the residents' demand for health resources.…”
Section: Selection Of Influencing Factorsmentioning
confidence: 99%
“…These results indicate that each hospital can achieve the basic requirements of CR and set up the CR program according to their own situation. There is a huge gap in medical insurance policies across China ( 35 ), and preceding studies have found that a lack of medical insurance is an obstacle to CR ( 16 , 17 ). However, this study shows that both the medical insurance coverage and the reimbursement rate do not affect the quality of CR.…”
Section: Discussionmentioning
confidence: 99%
“…However, medical resources are not only a reflection of these singular indexes, but are also closely related to financial resources, material resources, and manpower for healthcare. Therefore, some researchers have employed the entropy method [34] to comprehensively evaluate healthcare resources, but these methods are mostly applied at the provincial scale in China; the data are not easily available at the municipal level. Thus, taking into account the availability of data and the applicability of the method, this paper employs the fully arrayed polygonal graphical indication method [29] to comprehensively evaluate the level of medical and health resources by selecting three indicators: the number of hospital beds per thousand people, the number of medical and health institutions per thousand people, and the number of hospitals per hundred square kilometers.…”
Section: Introductionmentioning
confidence: 99%